Teaching the question, teaching the Shoah: understanding History from questioning subjectivities - Núñez Rojas, Mauricio Alejandro; González Mella, Bernardo (Clio. History and History Teaching, 2021)
Can we resist death? The question seeks to create reflection and debatein didactics of the Shoah on a controversial problem that emerges from the interaction in history classes. In one of them, a student reacts to a film image of violence in a ghetto by exclaiming “Why did they let them beat them, kill them? Why didn't they do something?" Hence the questions arise around the dialogue associated with trying to understand the history of the Holocaust, putting oneself in the place of its actors, developing historical empathy. Certainly, the teaching of the Shoah articulates an ethical-political education in people, but how are we supposed to teach the tragic human experience it entails? This article arises from the experiences of accompanying teachers in training where the question emerges as an articulator of dialogue and constructor of knowledge.